Multidimensional local theorem in the Knopfmachers semigroup - Skrabutėnas, Rimantas (Lietuvos matematikos rinkinys, 2007)
In the presentpaper a multidimensionallocal theorem for arithmetic functions definedin the Knopfmachers semigroup G is obtained.